An Attempt to Disperse the Italian Interlocking Directorship Network: Analyzing the Effects of the 2011 Reform - Carlo Drago; Roberto Ricciuti; Paolo Santella (Fondazione Eni Enrico Mattei (FEEM), 2015)
The purpose of this paper is to analyze the effects on the Italian directorship network of the corporate governance reform that was introduced in Italy in 2011 to prevent interlocking directorships in the financial sector. Interlocking directorships are important communication channels among companies and may have anticompetitive effect. We apply community detection techniques to the analysis of the networks in 2009 and 2012 to ascertain the effect of the reform. We find that, although the number of interlocking directorships decreases in 2012, the reduction takes place mainly at the periphery of the network whereas the network core is stable, allowing the most connected companies to keep their strategic position.
Keywords: C33; G34; G38; L14; 330; Interlocking Directorships; Corporate Governance; Community Detection; Social Networks